(untitled) (Research, Society and Development, 2021)
Feeding ruminants in arid and semi-arid regions has always been a challenge for producers, due to the edaphoclimatic conditions in these regions. The cactus pear is configured as a strategic food resource used in animal feeding in the aforementioned regions, this forage has morphophysiological characteristics that give it adaptation, in addition to high acceptability by ruminants, the cactus pear is considered an important source of energy and water for animals in times of water and food scarcity. However, its use exclusively or in large quantities can cause metabolic disorders, so this food resource must be associated with other foods rich in fiber and protein, such as gliricidia hay, thus resulting in the silage of two foods of complementary character adapted to the semiarid environment, which supplies animals with protein, energy and fiber in times of scarcity. Although the mentioned aspects, this new technology is still little known, both in the way of executing it and in relation to the parameters that involve the consumption of such silage by animals. Therefore, this review aims to provide information on the use of palm silage in association with gliricidia hay in the feeding of ruminants.